2022
DOI: 10.3390/life12050741
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Compound Eyes in Adults of Four Coleopteran Species Using Synchrotron X-ray Phase-Contrast Microtomography (SR-PhC Micro-CT)

Abstract: Compound eyes in insects are primary visual receptors of surrounding environments. They show considerable design variations, from the apposition vision of most day-active species to the superposition vision of nocturnal insects, that sacrifice resolution to increase sensitivity and are able to overcome the challenges of vision during lightless hours or in dim habitats. In this study, Synchrotron radiation X-ray phase-contrast microtomography was used to describe the eye structure of four coleopteran species, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Micro-CT is an innovative, promising method for investigating the internal anatomy of insects without time-consuming histological protocols, including dissections and serial sectioning (Betz et al 2007 ; Gutiérrez et al 2018 ; Sombke et al 2015 ). Accordingly, it has been applied for studying the morphology of different organs in adult insects, mainly focusing on the anatomy of the alimentary canal (Alba-Alejandre et al 2018 , 2019 , 2020 ), as well as the nervous (Donato et al 2021 ; Giglio et al 2022 ; Smith et al 2016 ) and reproductive (Alba-Alejandre et al 2020 ; Küpper et al 2019 ; Vommaro et al 2022 ) systems. Recently, virtual sectioning and 3D volumetric reconstructions, obtained from X-ray tube source, have been successfully used to describe the internal structures of the pupal stage and their volumetric and structural variations over time in a limited number of species (Helm et al 2018 ; Ikegami et al 2023 ; Lowe et al 2013 ; Nur et al 2019 ; Zhao et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Micro-CT is an innovative, promising method for investigating the internal anatomy of insects without time-consuming histological protocols, including dissections and serial sectioning (Betz et al 2007 ; Gutiérrez et al 2018 ; Sombke et al 2015 ). Accordingly, it has been applied for studying the morphology of different organs in adult insects, mainly focusing on the anatomy of the alimentary canal (Alba-Alejandre et al 2018 , 2019 , 2020 ), as well as the nervous (Donato et al 2021 ; Giglio et al 2022 ; Smith et al 2016 ) and reproductive (Alba-Alejandre et al 2020 ; Küpper et al 2019 ; Vommaro et al 2022 ) systems. Recently, virtual sectioning and 3D volumetric reconstructions, obtained from X-ray tube source, have been successfully used to describe the internal structures of the pupal stage and their volumetric and structural variations over time in a limited number of species (Helm et al 2018 ; Ikegami et al 2023 ; Lowe et al 2013 ; Nur et al 2019 ; Zhao et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, virtual sectioning and 3D volumetric reconstructions, obtained from X-ray tube source, have been successfully used to describe the internal structures of the pupal stage and their volumetric and structural variations over time in a limited number of species (Helm et al 2018 ; Ikegami et al 2023 ; Lowe et al 2013 ; Nur et al 2019 ; Zhao et al 2020 ). From a technical perspective, a significant advantage of the SR-PhC micro-CT analysis applied in our study is represented by the lack of sample staining by highly toxic chemicals such as uranyl acetate, iodine, phosphotungstic acid, and osmium tetroxide (Betz et al 2007 ; Metscher 2009 ; Smith et al 2016 ), while maintaining quality sample absorption and image contrast (Donato et al 2021 ; Giglio et al 2022 ; Heethoff and Cloetens 2008 ; Vommaro et al 2022 , 2023a ). The application of this technique for morphological studies of insects, including miniaturised species such as T. castaneum , allows the preservation of the overall spatial architecture of organs in their native orientation and the possibility to perform accurate, quantitative, morphometric measurements based on high-resolution image datasets and segmentation tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virtual dissections and volumetric reconstruction performed in our study indicated that the same qualitative and quantitative information can be obtained using SR‐PhC micro‐CT imaging, avoiding time‐consuming protocols for sectioning and staining tissues and limiting the inevitable tissue distortion caused by dissection. Body parts as small as the visual system (Giglio et al, 2022) and even the composition of the egg (Vommaro et al, 2022), can be easily studied using this technique, which is an alternative to conventional techniques for small and rare samples.…”
Section: Discussionmentioning
confidence: 99%
“…Synchrotron Radiation X‐ray phase‐contrast microtomography (SR‐PhC micro‐CT) is a powerful imaging technique for the study of anatomical structures and, when followed by an appropriate volumetric image segmentation, for 3D morphological analyses using an enhanced contrast‐to‐noise ratio in biological tissues, and does not require the use of contrast agents even in samples with weak X‐ray absorption (Donato et al, 2017; Elfarnawany et al, 2017; Endrizzi et al, 2018; Hellerhoff et al, 2019; Lak et al, 2008; Oliva et al, 2020). In previous entomological studies, virtual dissections performed using microtomography (micro‐CT) have provided morphological descriptions of various anatomical parts such as head (Betz et al, 2007; Hörnschemeyer et al, 2002), muscles (Bäumler et al, 2018; Li et al, 2011), brain (Smith et al, 2016), digestive (Alba‐Alejandre et al, 2019; Donato et al, 2021) visual (Giglio et al, 2022), and reproductive (Alba‐Alejandre et al, 2020; Küpper et al, 2019; Vommaro et al, 2022) systems. This non‐invasive method enhances the visualization of structures in situ and avoids all the artefacts associated with dissections and preparation of histological sections using traditional histological techniques, reducing the time of sample preparation protocols (Betz et al, 2007; Donato et al, 2021; Westneat et al, 2008).…”
Section: Introductionmentioning
confidence: 99%